Oxidative stress in periodontitis and the application of antioxidants in treatment: a narrative review - Liu, Wei; Guo, Daoyu (Frontiers in Physiology, 2025)
Periodontitis has turned into a general oral disease defined by chronic inflammation of the gums and helping tissues of the teeth. It dramatically influences both oral and systemic health and is a main trigger of tooth loss. Periodontitis is tightly linked to oxidative stress, and evidence reveals the utilization of certain antioxidants in related treatments. Our review delves into literature in periodontitis, centering on the latest therapeutic strategies and mechanistic evidences. This review starts by depicting the epidemiological features and pathogenic mechanisms of periodontitis, highlighting the vital mechanism of microbial community modefications, host immune responses, and genetic factors in disease development. Existing treatment approaches for periodontitis involve mechanical cleaning, antibiotic therapy, surgical interventions, and pharmacological treatments, with a comprehensive exploration on the strengths and limitations of each strategy and their related clinical utilizations. Besides, this review investigates emerging therapies, like anti-inflammatory treatments, immune modulation therapies, and biotechnological utilization in the control of periodontitis. It particularly stresses the protective effects of antioxidants and their mechanistic researches in periodontitis, highlighting their potential in slowing inflammatory responses and boosting tissue repair. Ultimately, our review intends to the concept of individual therapy and investigates future directions, comprising the utilization of precision medicine in periodontitis control and the individual design of treatment utilization.